Behavioural strategy of common bottlenose dolphins (Tursiops truncatus) in response to different kinds of boats in the waters of Lampedusa Island (Italy). Issue 5 (10th May 2013) - La Manna, G.; Manghi, M.; Pavan, G.; Lo Mascolo, F.; Sarà, G.
ABSTRACT: Owing to the increase of boat‐traffic in the ocean many studies have been conducted to determine the response of bottlenose dolphin ( Tursiops truncatus ) to this kind of disturbance. This species is affected by boats in various ways and the response depends on the behavioural state of the dolphin but also on the kind of vessel. This study aimed to determine the effect of motorboats and trawlers on dolphins' presence, permanence in the area and whistle parameters in Lampedusa waters (Italy). Sampling was carried out between May and December 2006 and between July and September 2009, using experimental passive acoustic monitoring systems (PAM); a total of 300 h of recordings and 3000 whistles were analysed. The dolphins' behavioural strategies depend on the kind of boats: in the case of motorboats, dolphins preferred to leave the area as the disturbance became too heavy to be tolerated; in the case of trawlers, dolphins changed their acoustic behaviour to compensate for the masking noise. The study highlighted the efficacy of PAM to detect the behavioural response of dolphins, suggesting a novel approach to assessing anthropogenic influences on marine mammal vocalizations in the absence of visual observations. Copyright © 2013 John Wiley & Sons, Ltd.